Gender and residence in focus: A cross-sectional analysis of sexsual violence among University Students in Bengkulu - Kosvianti, Emi; Wati, Nopia; Pratiwi, Bintang Agustina; Febriani, Cantika Alya Dwy (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Sexual violence is an ongoing public health problem in Indonesia, including in the university environment. This study aims to analyze the relationship between gender, residential status, and experiences of sexual violence among students in Bengkulu City. Method: The method used is quantitative with analytical observational design, involving 525 randomly selected respondents. Data were collected through online surveys at state and private universities in Bengkulu. Results: The results of the analysis showed that although women are more vulnerable to becoming victims of sexual violence, there was no significant relationship between gender and the experience of sexual violence (p = 0.138) >0.05. In addition, students who live in boarding houses have a higher risk, but there is no significant relationship between residential status and the experience of sexual violence (p = 0.720) >0.05. Conclusion: This study concludes that gender and place of residence are not significantly associated with experiences of sexual violence among students in Bengkulu, emphasizing the need for broader prevention strategies and further research into other contributing factors.